2003
DOI: 10.1016/s0304-3959(02)00299-3
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain processing of cutaneous pain in patients with chronic migraine

Abstract: Syndromes with chronic daily headache include chronic migraine (CM). The reason for the transformation of migraine into chronic daily headache is still unknown. In this study, we aimed to evaluate heat pain thresholds and event-related potentials following CO(2)-laser thermal stimulation (LEPS) in hand and facial regions in patients with CM, to show changes in nociceptive brain responses related to dysfunction of pain elaboration at the cortical level. The results were compared with findings from normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
66
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 16 publications
14
66
0
3
Order By: Relevance
“…By contrast, in a group of 25 CM patients, a trend for an excessive increase in LEP N2-P2 amplitudes was detected at baseline [9]. This is less pronounced when the stimulus becomes painful and with increasing disease duration.…”
Section: Pain-related Responsesmentioning
confidence: 63%
See 1 more Smart Citation
“…By contrast, in a group of 25 CM patients, a trend for an excessive increase in LEP N2-P2 amplitudes was detected at baseline [9]. This is less pronounced when the stimulus becomes painful and with increasing disease duration.…”
Section: Pain-related Responsesmentioning
confidence: 63%
“…However, LEPs are abnormally modulated by heterotopic conditioning stimuli such as remote capsaicin application [8] and by distraction [9,10].…”
Section: Pain-related Responsesmentioning
confidence: 99%
“…rs connectivity caudate-insula; % putamen-insula [132] % activation dorsolateral pons [47] %% iron content PAG and globus pallidus (T2) [29,31] ! central pain modulation [133,134] no % of posterior circulation infarcts [104] Medication overuse headache ! metabolism and tissue density orbitofrontal cortex [48,50] !…”
Section: Episodic Migraine (Interictal)mentioning
confidence: 99%
“…In addition, no correlation was found between the effects of remote pain on trigeminal LEPs and Another explanation for the observed results is an altered cognitive processing of pain. In previous studies, migraine patients showed a defect in the attentive modulation of LEPs during an alternative cognitive task [4], so the direction of attention to the remote tonic pain induced by capsaicin may not be able to reduce the level of arousal and emotion toward the painful laser stimulation at the trigeminal level. In a further study, migraine patients did not show trigeminal N2-P2 complex reduction and changes of their cortical representation within the anterior cingulate cortex observed in non-migraine patients during homotopical painful stimulation concurrent with laser stimuli [11].…”
Section: Discussionmentioning
confidence: 94%
“…The diffuse noxious inhibitory control (DNIC) allows that the activity of pain-transmitting neurons in the spinal dorsal horn and in trigeminal nuclei can be inhibited by noxious stimuli applied to body areas very remote from the excitatory fields of these neurons [4,5]. Recently a reduced effect of remote noxious stimuli on pain threshold tested by electrocutaneous stimuli administered either to the forearm (extra-cranial site) or to the temple (cranial site) was observed in chronic tension-type headache, suggesting a deficient DNIC-like pain inhibitory mechanisms in this type of chronic headache [6].…”
Section: Introductionmentioning
confidence: 99%